Admission Profile and Outcome of Patients in a Level III Intensive Care Unit: A Two-Year Comparative Study - Pathak, Sunil; Acharya, Subhash P; Acharya, Pragya; Bhattarai, Binita (Journal of Institute of Medicine Nepal, 2020)
Introduction An Intensive Care Unit (ICU) is an area where critically ill patients are admitted and the highest level of care is provided with close intensive monitoring and management. Clinical audit is a must to measure indicators of the quality of care in ICU and benchmarking outcome. The main aim of the study was to evaluate the profile of patients admitted to ICU and assess their outcome of two consecutive years. Methods A single-institutional, descriptive cross-sectional study was conducted on all adult patients admitted to the ICU of Tribhuvan University Teaching Hospital, Kathmandu, between April 2018 and April 2020 (Baisakh 2075 to Chaitra 2076). Results With an average of 1.98 admissions per day, a total of 1447 patients were admitted to TUTH ICU over the period of two years. A male preponderance was noted with a male to female ratio of 1.19:1. Most of the patients admitted were neurosurgical cases 429 (29.6%). A total of 884 (61%) were shifted out of ICU in stable condition while the overall mortality was 458 (31.6%). Conclusion This study shows that there is a higher severity of illness at admission as well as a comparatively high mortality rate. More number of patients were male, of age group of 15-65 years, with medical and neurosurgical conditions. This study of profile and outcome of patients admitted in ICU can serve as a quality indicator as well as evidence on which planning and policymaking can be based upon in the future.